What Has Come out from Phytomedicines and Herbal Edibles for the Treatment of Cancer?. (5th September 2018) - Bonam, Srinivasa Reddy; Wu, Yuan Seng; Tunki, Lakshmi; Chellian, Ranjithkumar; Halmuthur, Mahabalarao Sampath Kumar; Muller, Sylviane; Pandy, Vijayapandi
Abstract: Several modern treatment strategies have been adopted to combat cancer with the aim of minimizing toxicity. Medicinal plant‐based compounds with the potential to treat cancer have been widely studied in preclinical research and have elicited many innovations in cutting‐edge clinical research. In parallel, researchers have eagerly tried to decrease the toxicity of current chemotherapeutic agents either by combining them with herbals or in using herbals alone. The aim of this article is to present an update of medicinal plants and their bioactive compounds, or mere changes in the bioactive compounds, along with herbal edibles, which display efficacy against diverse cancer cells and in anticancer therapy. It describes the basic mechanism(s) of action of phytochemicals used either alone or in combination therapy with other phytochemicals or herbal edibles. This review also highlights the remarkable synergistic effects that arise between certain herbals and chemotherapeutic agents used in oncology. The anticancer phytochemicals used in clinical research are also described; furthermore, we discuss our own experience related to semisynthetic derivatives, which are developed based on phytochemicals. Overall, this compilation is intended to facilitate research and development projects on phytopharmaceuticals for successful anticancer drug discovery. Abstract : The fight in phytomedicines : We have compiled extensive information regarding medicinal plants and their bioactive compounds reported to have anticancer activity based on preclinical and clinical studies. Herein we also list some plant extracts that, when co‐administered with certain chemotherapeutic agents, synergize the overall anticancer activity. Certain plant extracts that consist of more than one bioactive phytoconstituent show significant anticancer activity by inhibiting multiple mechanisms that promote the progression and spread of cancer.